A mechatronic system for achieving optimum alignment of lower limb prosthesis - Tee, Kian Sek (2011)
Misalignment in the lower limb prosthesis can cause great discomfort in the stumpsocket interface and disturbance to gait function. In the long run, it could deteriorate the musculoskeletal system. In practice, the assessment still depends heavily on the verbal feedback of an amputee and experiences of a prosthetist. Moreover it is inconsistent amongst the prosthetists. Prosthetic alignment involves the adjustment of the prosthetic components relative to the gait quality. Some methods were proposed, including symmetry index, variation in a step-to-step transition, stability within the zone of integrated balance, matching roll-over shape (ROS) to an ideal ROS and etc. It is not clear if the optimum alignment could be achieved. These methods exhibit a few limitations, i.e. limited use of gait variables in a single comparison and non-uniform results when different gait variables are applied. There is a need to provide an objective assessment method that processes high dimensional gait variables and presents them in a simple form. In addition, it could be impractical and expensive clinically to spend excessive time on a patient. An ambulatory gait measurement system could achieve this objective to a certain extent. This research investigates a potential engineering solution that is able to provide an assistive and objective assessment of the lower limb prosthetic alignment that provides optimal gait quality. The effort includes a development of a low-cost ambulatory gait measurement system which could be reliably used during indoor and outdoor trials. Human walking trials using the designed ambulatory system are designed and performed to justify the proposed solution. A novel gait analysis method using Principle Component Analysis and Self-Organizing Feature Map is proposed to process high dimensional gait data into a simple plot and a decision guide. The proposed methodology could help to collect sufficient gait data during indoor and outdoor gaits and could provide an objective gait assessment during the application of lower limb prosthetic alignments.